2019
DOI: 10.1039/c8nr07974a
|View full text |Cite|
|
Sign up to set email alerts
|

High performing AgNW transparent conducting electrodes with a sheet resistance of 2.5 Ω Sq−1 based upon a roll-to-roll compatible post-processing technique

Abstract: A report of transparent and conducting silver nanowires (AgNWs) that produce remarkable electrical performance, surface planarity and environmental stability is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 26 publications
(40 reference statements)
1
41
0
Order By: Relevance
“…The transparencies of the nanocomposite electrodes were 84% and 83% for TNE10 and TNE20, respectively, compared with 87% for an acrylic film electrode (AE), at a sheet resistance of 12.4–15.6 Ω sq −1 . The transparencies of the nanocomposite electrodes were comparable to those of other reported transparent electrodes based on AgNW–PET (88.8% vs 12.1 Ω sq −1 ) and ITO–glass (84% vs 12 Ω sq −1 ) and were superior to those of electrodes based on ITO–PET (85% vs 40 Ω sq −1 ), CNT–PET/polyethylene naphthalate (PEN)/cycloolefin polymer film Zeonor (optimum 84% vs 60 Ω sq −1 ), pristine graphene–glass (90% vs 352.7 Ω sq −1 ), and modified graphene–glass (89% vs 91.4 Ω sq −1 ) (see Figure S4 in the Supporting Information). In fact, the prospect of improving the electro‐optical property of the AgNW electrodes is endless with the development of new processing strategies.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The transparencies of the nanocomposite electrodes were 84% and 83% for TNE10 and TNE20, respectively, compared with 87% for an acrylic film electrode (AE), at a sheet resistance of 12.4–15.6 Ω sq −1 . The transparencies of the nanocomposite electrodes were comparable to those of other reported transparent electrodes based on AgNW–PET (88.8% vs 12.1 Ω sq −1 ) and ITO–glass (84% vs 12 Ω sq −1 ) and were superior to those of electrodes based on ITO–PET (85% vs 40 Ω sq −1 ), CNT–PET/polyethylene naphthalate (PEN)/cycloolefin polymer film Zeonor (optimum 84% vs 60 Ω sq −1 ), pristine graphene–glass (90% vs 352.7 Ω sq −1 ), and modified graphene–glass (89% vs 91.4 Ω sq −1 ) (see Figure S4 in the Supporting Information). In fact, the prospect of improving the electro‐optical property of the AgNW electrodes is endless with the development of new processing strategies.…”
Section: Resultssupporting
confidence: 77%
“…In previous studies, it has been reported that the introduction of polyethoxysiloxane or various nanoparticles of TiO 2 , Al 2 O 3 , SiO 2 , ZrO 2 , and ZnO into the AgNW layer can improve the thermal stability of the electrodes by minimizing thermal oxidation of the AgNWs, sometimes at the expense of a reduction in transparency . In our study, we successfully demonstrated a high‐thermal‐performing AgNW electrode with good electro‐optical performance by developing a thermal dimensionally stable nanocomposite substrate that minimized the fragmentation of AgNWs.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…To overcome these disadvantages, studies on the development of metallic nanowires have been actively conducted to increase the density of conducting pathways while reducing contact resistance. In a recent study, Kumal et al developed synthesized AgNWs with a low sheet resistance down to 2.5 Ω sq −1 . To reduce junction contact resistance and synthesize AgNWs with a high‐density conductive network, ethanol was dispersed with AgNWs and formed on the substrate through spray coating, followed by three postprocessing steps, including thermal embossing, photonic sintering, and N 2 plasma treatment.…”
Section: Advanced Strategies For Wearable Smart Sensing Systems Basedmentioning
confidence: 99%